On the Role of Acoustical Improvement and Surface Morphology of Seashell Composite Panel for Interior Applications in Buildings - Erni Setyowati; Gagoek Hardiman; Purwanto; Mochamad Arief Budihardjo (Buildings, 2019)
This manuscript focuses on the acoustical behaviors and surface morphology of seashell waste filler reinforced polyester (SFRP) coverings Anadara granosa Linn, Perna viridis Linn, and Placuna placenta Linn and applications in buildings. Their acoustical performances were observed using an impedance tube using a technique with two and four microphones based on ASTM E1050-98 and ASTM E2611-09. The improvements of acoustical performance were conducted by a coupled resonator inclusion with addition of a fibrous dacron layer and back cavity. The experimental results showed that the resonators and back cavity on the material structure were able to shift the absorption ability at low frequency. The promising wide broadband frequencies performance occurred when the 15 mm Placuna placenta FRP treated with front-tailed cavity without any additional fibrous layer and air gap started from 0.2 at 2.0 kHz. The combination of resonators and fibrous layer on the material structure was able to stabilize the sound transmission loss (STL) in 52–56 dB at a high frequency. On the observation of the simple surface morphology material, it was found that Placuna placenta Linn had the highest damping performances due to the smallest pores and the most carbon compound compared to the others. Therefore, this finding is very useful for building applications.